1994
DOI: 10.1152/ajpcell.1994.267.2.c514
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of the sorbitol permease in PAP-HT25 cells

Abstract: The sorbitol permease enables the efflux of sorbitol from cultured rabbit papillary cells (PAP-HT25) in response to a reduction in osmolality. The anion transport inhibitor 5-nitro-2-(3-phenylpropylamino)benzoate (100 microM) inhibited efflux by 92%, and 4,4'-diisothiocyanostilbene-2,2'-disulfonic acid (0.5 mM) reduced efflux by 40%. 2,4-Dinitrobenzenesulfonate and p-chloromercuriphenylsulfonic acid had no effect. The protease trypsin (0.05 mg/ml) reduced sorbitol efflux by 53%, pronase (0.01 mg/ml) by 47%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The size of the substrate is certainly an important factor, with an estimated pore diameter of 0.8‐0.9 nm. However, the rate of polyol permeation is also influenced by the presence and arrangement of hydroxyl groups on the solute, suggesting significant interaction between the channel protein and the permeating solute (Napathorn & Spring, 1994). Similarly, it has been observed that swelling‐activated channels have a higher permeability to β‐amino acids than to similarly sized α‐amino acids (Pasantes‐Morales et al 1994; Roy, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The size of the substrate is certainly an important factor, with an estimated pore diameter of 0.8‐0.9 nm. However, the rate of polyol permeation is also influenced by the presence and arrangement of hydroxyl groups on the solute, suggesting significant interaction between the channel protein and the permeating solute (Napathorn & Spring, 1994). Similarly, it has been observed that swelling‐activated channels have a higher permeability to β‐amino acids than to similarly sized α‐amino acids (Pasantes‐Morales et al 1994; Roy, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…44). With respect to organic solutes, hypotonicity-inducible efflux of sorbitol (18,21,39) and inositol (26,27,33,50,51) has been extensively characterized in cultured cells of the renal medulla and brain, respectively. The signaling events leading to activation of inorganic ion and organic solute efflux pathways remain obscure.…”
mentioning
confidence: 99%
“…An inhibition with structural analogs could not be observed [13, 14]. In addition, sorbitol uptake in plasma membrane vesicles from the thick ascending limb of Henle [15]and astrocytes showed no saturation [16].…”
Section: Discussionmentioning
confidence: 99%
“…This cooperation, however, requires a regulated sorbitol release from the basolateral side of IMCD cells and a sorbitol uptake into interstitial cells. The osmotically regulated sorbitol release was extensively investigated by several study groups [3, 6, 13]. However, a sorbitol uptake into renal cells was neither assumed nor examined.…”
Section: Introductionmentioning
confidence: 99%